2017
DOI: 10.1016/j.ijscr.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Gastric outlet obstruction by a lost gallstone: Case report and literature review

Abstract: HighlightsGallstones may be lost in a laparoscopic cholecystectomy and cause morbidity.Diagnosis of complications are difficult.Findings may be mistaken for malignancies unless clinical suspicion remains high.Inflammation from lost stones can obstruct the lumen of the gastrointestinal tract.Lost gallstones are best managed during the initial cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Bouveret’s Syndrome, is a distinct entity in which gastric outlet obstruction (GOO) develops after impaction of a large gallstone in the duodenum or pyloric channel usually secondary to a cholecystoenteric fistula [3]. However, iatrogenic cases of both conditions have been reported following laparoscopic cholecystectomy and endoscopic retrograde cholangiopancreatography (ERCP) with sphincterotomy [[4], [5], [6]].…”
Section: Introductionmentioning
confidence: 99%
“…Bouveret’s Syndrome, is a distinct entity in which gastric outlet obstruction (GOO) develops after impaction of a large gallstone in the duodenum or pyloric channel usually secondary to a cholecystoenteric fistula [3]. However, iatrogenic cases of both conditions have been reported following laparoscopic cholecystectomy and endoscopic retrograde cholangiopancreatography (ERCP) with sphincterotomy [[4], [5], [6]].…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen(20%) of authors reported the number of discovered gallstones [ 18 , 25 , 27 29 , 31 , 35 , 38 , 39 , 44 , 45 , 50 , 54 , 57 , 70 , 80 , 83 ]. The size of discovered gallstones was reported by 12(14.11%) authors [ 18 , 19 , 25 , 28 , 31 , 35 , 37 , 52 , 63 ]. The most prevalent presenting symptoms were pain, fever, nausea, vomiting, abdominal swelling, fistula formation, and loss of weight.…”
Section: Resultsmentioning
confidence: 99%